Estudio de factibilidad para el uso de internet con (SDN) en la ciudadela “valle verde 2, etapa 1” del cantón Babahoyo. - Torres Segura, Arielle Ámbar (2024)
The study focuses on evaluating the feasibility of using Software Defined Networking (SDN) in the private citadel "Valle Verde 2, Stage 1” in Babahoyo, with the aim of improving internet access to residents. Through the analysis of the existing network infrastructure, the evaluation of Internet demand and the determination of bandwidth and quality of service (QoS) requirements, which seeks to optimize connectivity and information management in this community. The research highlights how. The implementation of SDN can enable centralized and dynamic network management, which would mean higher quality of service by adapting to traffic variations imposed by users' quality demands. Although the physical aspects of the infrastructure have improved significantly, network management remains a challenge. The traditional way of managing the network does not have the ability to dynamically adjust to the variability of user demands and link utilization. Therefore, I advocate the implementation of SDN as it is an innovative solution to provide a more flexible and efficient network architecture. SDN provides centralized network management, meaning better utilization of the link by allowing dynamic adjustments and ramping up or down based on changes in real-life traffic.